1995
DOI: 10.1002/ana.410380307
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral fetal nigral transplantation into the postcommissural putamen in Parkinson's disease

Abstract: We performed fetal nigral transplantations in 4 Parkinson's disease (PD) patients. Solid grafts were bilaterally implanted into the postcommissural putamen using 3 to 4 donors per side aged 6 1/2 to 9 weeks postconception. Transplant deposits were separated by no more than 5 mm in three dimensions. Cyclosporine was employed for a total of 6 months. Patients were evaluated at baseline and at 1, 3, and 6 months postoperatively. Striatal 18-fluorodopa uptake was assessed by positron emission tomography at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 393 publications
(181 citation statements)
references
References 52 publications
4
176
0
1
Order By: Relevance
“…Neural transplantation of fetal ventral mesencephalic (VM) dopaminergic neurons has been introduced in the clinic as an alternative treatment for PD (Lindvall et al, 1988(Lindvall et al, , 1992Madrazo et al, 1988;Freeman et al, 1995;Kordower et al, 1995;Borlongan et al, 1999;Borlongan, 2000). However, recent clinical trials have generated mixed results in that transplantation of fetal VM cells was shown to induce dyskinesia in some patients (Freed et al, 2001;Olanow et al, 2003), whereas excellent graft dopaminergic reinnervation of the parkinsonian affected striatum accompanied positive clinical improvements in transplanted patients who did not develop dyskinesia (Mendez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Neural transplantation of fetal ventral mesencephalic (VM) dopaminergic neurons has been introduced in the clinic as an alternative treatment for PD (Lindvall et al, 1988(Lindvall et al, , 1992Madrazo et al, 1988;Freeman et al, 1995;Kordower et al, 1995;Borlongan et al, 1999;Borlongan, 2000). However, recent clinical trials have generated mixed results in that transplantation of fetal VM cells was shown to induce dyskinesia in some patients (Freed et al, 2001;Olanow et al, 2003), whereas excellent graft dopaminergic reinnervation of the parkinsonian affected striatum accompanied positive clinical improvements in transplanted patients who did not develop dyskinesia (Mendez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation of stem cells into diseased nervous tissue (or by peripheral administration) could provide beneficial effects by introducing a reservoir of progenitor cells with the potential to distribute widely in the brain and differentiate into missing neuronal phenotypes, or by trophic factor support rescuing degenerating endogenous cells [8,10,11,17,31,33,41]. The cell transplantation approach has already been implemented as clinical trials for the treatment of Parkinson's disease [15,35,36] or stroke [1,27,34]. While the results of these studies were encouraging, it became clear that more basic research needs to be done before we can expect spectacular clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic Grafts Can Survive and Become Morphologically Integrated in the PD Patient's Brain Following implantation of postmitotic DA neuroblasts from the ventral mesencephalon of 6-to 9-weekold human fetuses, positron emission tomography (PET) detected increases in 6-L-[ 18 F]-fluorodopa ( 18 F-dopa) uptake ( Fig. 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and histopathological studies have shown long-term, extensive synaptic reinnervation in the striatum [13,[20][21][22][23][24][25][26][27].…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 99%